Exciton‐ and Polaron‐Induced Reversible Dipole Reorientation in Amorphous Organic Semiconductor Films. Issue 8 (21st February 2019) - Deng, Chao; Zhang, Liwei; Wang, Dan; Tsuboi, Taiju; Zhang, Qisheng
Abstract: The quantum efficiency of organic light‐emitting diodes (OLEDs) employing thermally activated delayed fluorescence (TADF) highly depends on the S1 −T1 energy gaps (Δ E ST ) of the emitters. However, the Δ E ST values determined in solution or even in organic thin films through a static approach continuously fail in predicting device performance. Herein, by systematically investigating the time‐resolved emission spectra of several TADF emitters in various matrixes and the dielectric spectra of the matrixes, it is demonstrated that molecular organic semiconductors can undergo reversible and irreversible spatial rearrangements within a few dozen nanoseconds in an electric field created by a polarized charge‐transfer state and can in turn lower the excited‐state energy. In contrast to solution solvation, the polarized microenvironment in films can last for tens of microseconds or more after removing the electric field, leading to a narrowing and a broader distribution of Δ E ST . In TADF OLEDs, the large dipole moment of emitter‐based polarons is key for reducing the Δ E ST of subsequently generated excitons by inducing the dipole orientation of the surrounding molecules. Understanding the so‐called solid‐state solvation with a dynamic approach can provide deeper insight into the working mechanism in organic semiconductor devices. Abstract : The dipole moment of thermally activated delayed fluorescence (TADF) molecules in the excited state induces reversible and irreversible spatial rearrangements of the surrounding molecules within a few nanoseconds and in turn lowers the excited‐state energy. However, the disorientation process is much slower after the molecular electronic polarizability diminishes, providing an effective way to reduce the Δ E ST of TADF molecules in solid.